Periodontal Diseases and the Risk of Metabolic Syndrome: An Updated Systematic Review and Meta-Analysis - Gobin, Romila; Tian, Dan; Liu, Qiao; Wang, Jianming (Frontiers in Endocrinology, 2020)
Background Periodontitis and metabolic syndrome (MetS) are two major global health problems that are widely prevalent in the world, although the former is a common but neglected infection in developing countries and the other is a non-infectious but prevalent disease in developed countries. The association between periodontitis and MetS has become an important topic of research in the scientific literature. The aim of this study is to have an update on the evaluation of the existence and magnitude of the relationship between periodontal disease and the risk of MetS, through a systematic review and meta-analysis. Methods We searched PubMed, Web of Science, ScienceDirect, Chinese National Knowledge Infrastructure, and Wanfang database for original studies assessing the association between periodontitis and MetS published before August 2019. A random effect model was conducted to estimate the pooled crude or adjusted odds ratio (OR) with 95% confidence interval (95% CI) to establish the strength of association. Subgroup analysis was performed by considering the diagnosis method or countries. Results We identified 43 potentially eligible articles for this systematic review and meta-analysis, including 32 cross-sectional studies, 8 case-control studies and 3 cohort studies. Among them, 39 articles presented enough information for the meta-analysis. The pooled crude and adjusted ORs were 1.99 (95% CI: 1.75- 2.25) and 1.46 (95% CI: 1.31-1.61), respectively. Subgroup analysis showed a consistent relation either stratified by diagnosis method or by countries. Conclusion Our results show compelling evidence of the association between periodontitis and MetS. Patients with periodontal disease are the key screening population for MetS. We also recommend that anyone exhibiting several components of MetS should receive a dental and periodontal check-up, along with a general health examination.